Dysfibrinogenemia: from molecular anomalies to clinical manifestations and management. (2nd May 2015) - Casini, A.; Neerman‐Arbez, M.; Ariëns, R. A.; de Moerloose, P.
Summary Congenital dysfibrinogenemia is a qualitative congenital fibrinogen disorder characterized by normal antigen levels of a dysfunctional fibrinogen. The diagnosis is usually based on discrepancies between fibrinogen activity and antigen levels, but could require more specialized techniques for the assessment of fibrinogen function, owing to some limitations in routine assays. Molecular abnormalities, which are frequently heterozygous missense mutations localized in exon 2 of FGA and exon 8 of FGG, lead to defects in one or more phases of fibrinogen to fibrin conversion, fibrin network formation, and other important functions of fibrinogen. The clinical phenotype is highly heterogeneous, from no manifestations to bleeding and/or thrombotic events. Asymptomatic propositi and relatives with the predisposing genotype are at risk of developing adverse outcomes during the natural course of the disease. Correlations between genotype and phenotype have not yet been clearly established, with the exception of some abnormal fibrinogens that severely increase the risk of thrombosis. Functional analysis of polymerization and fibrinolysis, structural studies of the fibrin network and the viscoelastic properties of fibrin clot could help to predict the phenotype of congenital dysfibrinogenemia, but have not yet been evaluated in detail. The management is essentially based on personal and family history; however, even individuals who are still asymptomatic and without a family history should be carefully assessed and monitored. Particular situations, such as pregnancy, delivery, and surgery, require a multidisciplinary approach.